COMPARATIVE ANALYSIS OF BUSINESS PROCESSES SIMULATION SYSTEMS BY FUNCTIONAL COMPLETENESS CRITERION - Yury A. Rvantsov (Advanced Engineering Research, 2011)
Case study of functional completeness analysis to compare imitation modeling systems, and to define their conformity with the user requirements is offered.